Identification of objects priority for conducting energy monitoring - Borichenko, Olena; Cherniavskyi, Anatolii (Technology audit and production reserves, 2018)
The object of research is the energy monitoring system. To achieve a high level of energy efficiency in any enterprise, it is necessary to periodically evaluate the level of effectiveness of energy saving activities, that is, to carry out energy monitoring. One of the most problematic places in creating energy monitoring systems is the prioritization of facilities for which it is possible and appropriate to monitor. When determining the objects for which it is expedient to create an energy monitoring system, it is necessary to take into account the basic requirements that such facilities should meet. Among such requirements: the location of objects in one or adjacent premises, a single technological process and the management of these objects of a small number of operators. In accordance with these requirements, an algorithm for selecting objects for creating an energy monitoring system is proposed. At the first stage all equipment of the enterprise should be divided into a small number of groups on a technological basis. The next step is building energy consumption balances separately for each of the technological processes of production of all types of enterprise products. To compile energy consumption balances, a methodology for constructing optimal energy balance models can be applied. Based on the calculated values of energy consumption for the production of each type of product, equipment can be distributed into smaller groups based on two criteria. These criteria include the location of equipment and their power supply from the same power points. The resulting equipment groups are the previous objects, but this does not mean that an energy monitoring system is appropriate for such facilities. In this paper, solution of additional problems is proposed, in particular: determination of the composition of factors that affect the amount of energy consumption; expediency of installing additional meters for energy consumption, production and other parameters; estimation of monetary expenses for creation of systems; estimation of energy saving potential; financial analysis of the feasibility of creating systems. Thanks to this, it is possible to reasonably determine the objects for which it is technically possible and financially feasible to create an energy monitoring system.